(untitled) (LEARNing Landscapes, 2011)
In this article I discuss a learning task adapted for the college classroom in which students learn about the parts and functions of the brain by designing a robot’s brain. This task is based on a four-phase model (engage, inform, practice, and feedback) of instructional design outlined by McAlpine (2004). I describe the four phases in relation to this learning task and provide samples of student feedback. I conclude with a discussion of how this model maximizes student learning.